2015
DOI: 10.3389/fendo.2015.00133
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 and Cardiac Physiopathology

Abstract: The heart is not traditionally considered either a target or a site of fibroblast growth factor-21 (FGF21) production. However, recent findings indicate that FGF21 can act as a cardiomyokine; that is, it is produced by cardiac cells at significant levels and acts in an autocrine manner on the heart itself. The heart is sensitive to the effects of FGF21, both systemic and locally generated, owing to the expression in cardiomyocytes of β-Klotho, the key co-receptor known to confer specific responsiveness to FGF2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 59 publications
3
92
0
2
Order By: Relevance
“…Experimentally induced myocardial hypertrophy or infarction lead to increased expression of FGF21 (ref. 97 ), which might prevent further progression of myocardial damage.…”
Section: Adiponectinmentioning
confidence: 99%
“…Experimentally induced myocardial hypertrophy or infarction lead to increased expression of FGF21 (ref. 97 ), which might prevent further progression of myocardial damage.…”
Section: Adiponectinmentioning
confidence: 99%
“…However, later studies showed that FGF21 is expressed and secreted by cardiac cells in response to various stress conditions, including obesity, type 1 diabetes, fasting, ER stress, inflammation, infarct or hypertrophy, and some cardiovascular diseases [49,50]. In the heart, FGFR1 and KLB have been detected in cardiac cells, where FGF21 exerts protective effects in an autocrine and endocrine fashion.…”
Section: Heart: Fgf21 Exerts Cardioprotective Actionsmentioning
confidence: 99%
“…In the heart, FGFR1 and KLB have been detected in cardiac cells, where FGF21 exerts protective effects in an autocrine and endocrine fashion. The mRNA expression of FGF21 in these cells is driven by the transcriptional activation of Sirtuin1 -peroxisome proliferator-activated receptor a (Sirt1-PPARa) [50]; however, it can also be regulated by ATF4, especially when FGF21 induction is caused by ER or oxidative stress [49,51].…”
Section: Heart: Fgf21 Exerts Cardioprotective Actionsmentioning
confidence: 99%
See 2 more Smart Citations